Growth and breeding performance of broodfish and larval growth of Heteropneustes fossilis with feeds (Annals of Bangladesh Agriculture, 2022)
A 63-day long indoor experiment was carried out to determine the effects of four different diets of: live tubificid worms (T1), live tubificid worms with formulated feed (T2), shrimp with formulated feed (T3) and formulated feed (T4) on brood development and larval growth of Heteropneustes fossilis. Broodfish were fed twice a day with experimental diets. Reproductive performance of H. fossilis was evaluated based on growth parameters and fry production of broodstock. The result showed that while the highest (16.37 ± 0.90g) and the lowest (7.03 ± 0.85g) weight gain was obtained in T2 and T4 respectively, however, there was no significant difference between treatments T1 and T3. The FCR of T2 was found to be the lowest followed by T3, T1 and T4, respectively. The highest fecundity was found in T2 (4245.48 ± 347.38) followed by T3 (3747.10 ± 317.99), T1 (3583.96 ± 327.27) and T4 (3191.95 ± 444.55). The rate of hatching and their survival was significantly higher in T2 followed by T3, whereas T1 and T4 showed significantly lower hatching and survival rate. After 28 days of rearing, larvae obtained from T2 treatment showed the highest growth performance compared to other treatments. The findings of the current research suggested that live feed (tubificid worms) supplemented with formulated feed may enhance the breeding performance and larval growth of H. fossilis and could be considered an affordable option for small-scale hatcheries.Ann. Bangladesh Agric. (2021) 25 (2) : 13-25